2009
DOI: 10.1159/000213085
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease Is a Negative Predictor of 30-Day Survival after Acute Ischaemic Stroke

Abstract: Background/Aims: Impaired renal function is a strong risk factor for cardiovascular diseases and worsens a patient’s prognosis. Renal dysfunction predicts mortality after acute stroke in the long term. On the other hand, in-hospital mortality after acute stroke is strongly associated with disorders of consciousness at the onset of stroke, severity of stroke, body temperature, blood sugar and some other comorbidities. The aim of the study was to analyze the possible role of renal dysfunction and/or signs of ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
(45 reference statements)
2
25
0
Order By: Relevance
“…Carter et al 42 showed that the creatinine level was a predictor of mortality in patients with ischemic stroke. Hojs Fabjan et al 43 and Brzosko et al 44 showed that a low GFR was associated with a higher in-hospital mortality rate. Yahalom et al 26 showed that 45.1% of the patients in their series who had a GFR .60 mL per minute per 1.73 m 2 had an NIHSS score worse than 6, while 56.4% of the patients in their series with a GFR of 15 to 60 mL per minute per 1.73 m 2 showed a corresponding severity.…”
Section: Discussionmentioning
confidence: 99%
“…Carter et al 42 showed that the creatinine level was a predictor of mortality in patients with ischemic stroke. Hojs Fabjan et al 43 and Brzosko et al 44 showed that a low GFR was associated with a higher in-hospital mortality rate. Yahalom et al 26 showed that 45.1% of the patients in their series who had a GFR .60 mL per minute per 1.73 m 2 had an NIHSS score worse than 6, while 56.4% of the patients in their series with a GFR of 15 to 60 mL per minute per 1.73 m 2 showed a corresponding severity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that reduced eGFR is associated with a poor outcome in ischemic stroke patients (18,19), whereas other studies do not (20,21). Mittleman and colleagues (19) recently demonstrated that a reduced or highly elevated eGFR (,60 or .125 mL/min/1.73 m 2 ) was associated with a higher mortality rate compared with patients with moderate levels of eGFR in 1,175 acute ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies showed that low eGFR was associated with a higher in-hospital mortality rates. 3,34 Data from Nationwide Inpatient Sample study showed that among 1 million of stroke hospitalizations during the study period, 6.1% had a co-morbid diagnosis of CKD, and 9% of those with CKD died in hospital. Presence of CKD was independently associated with higher odds of dying during stroke hospitalization regardless of stroke type 8 .…”
mentioning
confidence: 99%